I went walking - Williams, Sue, 1948-; Vivas, Julie, 1947- (San Diego : Harcourt Brace & Co., 1990)
During the course of a walk, a young boy identifies animals of different colors.
"First published 1989 by Omnibus Books"--Colophon.
"Gulliver books."
Notable/Best Books (A.L.A.)
School Library Journal
School Library Media Quarterly (A.A.A.L.)
1.4
Keywords: Oversize books -- Specimens; Animals -- Fiction; Color -- Fiction; Oversize books; Stories in rhyme; Walking -- Fiction; Animals -- Fiction; Big books; Color -- Fiction; Stories in rhyme; Walking -- Fiction